2017
DOI: 10.1039/c7tc00382j
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency organic light-emitting diodes of phosphorescent PtAg2heterotrinuclear acetylide complexes supported by triphosphine

Abstract: Platinum(ii)–silver(i) heterometallic cluster complexes are used as a new type of phosphorescent dopant to achieve high-efficiency OLEDs with 67.4 cd A−1peak current efficiency (CE) and 17.4% external quantum efficiency (EQE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…[ 105,107,132,152–157 ] In contrast to the above mentioned, silver(I) complexes have scarcely been applied to lighting devices. [ 158–161 ]…”
Section: Organometallic Tadf Compounds For Lightingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 105,107,132,152–157 ] In contrast to the above mentioned, silver(I) complexes have scarcely been applied to lighting devices. [ 158–161 ]…”
Section: Organometallic Tadf Compounds For Lightingmentioning
confidence: 99%
“…Although palladium(II) and platinum(II) complexes are usually phosphorescent emitters, [ 12,160,188–197 ] some of them have also shown TADF behavior. [ 28,87,193,198–200 ] In 2015, Li reported vapor‐processed OLEDs based on two palladium(II) complexes Pd1 and Pd2 (Table 8 and Scheme ), featuring both phosphorescence and TADF emissions.…”
Section: Organometallic Tadf Compounds For Lightingmentioning
confidence: 99%
“…Although (hetero-)metallic clusters are beyond the scope of this review, it is worth to mention some recent reports from Chen and co-workers on trimetallic systems based on PtAu 2 [2122] and PtAg 2 [2324] core. Motivated by very high PLQYs in doped films, OLED devices were fabricated showing remarkable efficiency attaining EQE of 21.5% at a luminance of 1029 cd m −2 with small roll-off [21].…”
Section: Reviewmentioning
confidence: 99%
“…The trans -bisethynylbis­(trialkylphosphine)­platinum­(II) building block, [Pt] , is a versatile unit for the design of photonic materials showing potential applications in nonlinear optics and light-emitting diodes. In the field of solar cells, the [Pt] -containing materials are also active irrespective of whether they are used as molecules or within polymer chains. , Indeed, dye-sensitized solar cells and bulk heterojunction solar cells (BHJSCs) were designed. To the best of our knowledge, the highest photoconversion efficiency (PCE) was recently reported to be 5.29% for a BHJSC containing the [Pt] moiety. , Concurrently, studies on complexes bearing [Pt] units indicated that the charge separated states are formed in the short picosecond (ps) time scale and that the [Pt] unit could mediate the electron transfer. Over the years, it was suggested that anchoring diphenylamine pendants as electron-rich groups , and using the electron-deficient anthraquinone, AQ , moiety , should improve the PCEs of [Pt] -containing materials for solar cells.…”
Section: Introductionmentioning
confidence: 99%